PRATISARNEEYA KSHARA KARMA IN THE MANAGEMENT OF RECTAL PROLAPSE - A CASE STUDY - Premsukh; Amit Kumar (International Journal of Applied Ayurved Research, 2019)
Background: Rectal prolapsed is the disease in which rectal mucosa and submucosa with or without muscular layer are prolapsed out of anal verge partially or completely.The present case study was aimed to develop a cost effective, conducive para-surgical procedure in the management of rectal prolapse. Aim- to develop non surgical treatment modality in case of partial rectal prolapsed. Materials and Methods: Study was conducted on a female patient aged 48 yrs who was diagnosed as complete rectal prolapse, admitted in Shalya Tantra IPD, NIA, Jaipur. Procedure was performed under local anaesthesia. After reducing the prolapsed rectum the Apamarg teekshna pratisarneeyakshara was applied circumferentially on rectal mucosa by using a slit proctoscope & applicator.Kshara was applied for 2 min (100 Matrakala) till the colour of rectal mucosa was changed to pakwvajambuphalavarna, then the area was washed with distilled water followed by nimbu swarasa. The process was repeated 4 times to cover whole circumference of the rectal mucosa. Matravasti with Yashtimadhughrita was given twice daily for 7 days from first post procedure day followed by with Changeri ghrita twice daily for 15 days. Patient was advised pathyaapthya aahara-vihara. Observations and Results: Patient had relief from symptoms of rectal prolapse. No rectal prolapse was complained during follow up period. Conclusion:As surgery is an ultimate treatment in rectal prolapse with its own limitations, where Ksharakarma can be recommended as an emerging alternative to surgery with minimal post procedure complications. Kshara karma is a conducive, day care procedure and is very cost-effective.